The research of acute toxicity of 4-amino-5-(4-(tert-butyl)phenyl)-4H-1,2,4-triazoles-3-thiol derivatives - I. I. Аksyonova-Seliuk; Ye. S. Pruglo; O. I. Panasenko; Ye. G. Knysh (Zaporozhye State Medical University, 2017)
Introduction. The process of new drugs creating includes a plurality of stages, which allow their application in medical practice in the future. These studies are a guarantee of the effectiveness and safety of the test compounds. One of the most important stages of preclinical research is the research of acute toxicity. The data of this experiment gives an estimate of toxic effect of new compounds on the organism of experimental animals that allows to judge about expediency of application of these substances in diseases therapy. The aim of toxicological researches of 4-amino-5-(4-(tert-butyl)phenyl)-4H-1,2,4-triazoles-3-thiol's derivatives was to establish their damaging effect on the organism of experimental rats and identify possible influence of chemical structure on acute toxicity of the compounds. Methods and results. The tabular rapid-method by V. B. Prozorovsky was chosen. It's based on the test-compounds dosing according to a logarithmic scale. Two animals were used for the study of one dose of the compound. Animals were pre-weighed and labeled, also an assessment of their external condition was carried out. According to the results of the study, it was found that the compounds belong to the IV class of toxicity according to the classification of K. K. Sidorov. Conclusion. Assessment of toxicity of 31 new compounds, namely derivatives of 4-amino-5-(4-(tert-butyl)phenyl)-4H-1,2,4-triazoles-3-thiol was carried out. The experiments allowed to establish LD50 of test compounds. The most toxic and the least toxic compounds were found. The results of research make it possible to determine some "structure-action" dependence.